“Religious Freedom” as a Tool to Oppress: The Explosion in Religion-Based Attacks on Civil Rights in Litigation - Alex J. Luchenitser (Social Sciences, 2016)
Over the last half-decade, there has been an explosion in the United States of lawsuits in which claims to religious liberty have been used to justify abridging the civil rights of women, LGBTQ people, and other minorities. This article surveys such litigation in several areas: health-insurance coverage, healthcare services, marriage-related services, employment, and housing. For each area, the article analyzes recent litigation, compares it to earlier activity (if any), and discusses the kinds of arguments that have been made, how courts have responded to them, and how such arguments are likely to fare in the future. The article concludes that the ultimate fate of many of these kinds of cases will likely be determined by who the next member is of a U.S. Supreme Court that is currently split four-four between social liberals and conservatives.